Factor Influence Of Container Loading And Unloading As Productivity Support On Mirah Terminal - Sumarzen Marzuki; Rusi Aswidaningrum; Choirul Anam; Soedarmanto Soedarmanto (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This study aims to obtain a quantitative model that can be used to determine the factors that have a significant impact on loading and unloading productivity. Design/methodology/approach: The method used to solve the problem is multiple linear regression method and dummy variable. Findings: The number of samples for this analysis were all ships thats belong to PT Meratus Line which docked at the Mirah Terminal in Surabaya for 12 months, starting from January 2019 to December 2019. The response used is realization data in the number of containers per hour. The initial predictors that are thought to have an impact on productivity are operational personnel and loading and unloading workers, loading and unloading equipment readiness, work system, full empty ratio and total container weight. There are 4 steps to analyze the regression model that has been obtained. Simultaneous test (using P-value), individual test (t test), F test (simultaneous test), Glejser heteroscedasticity and heterocedasticity test, multicoreleation test, reliability test and validity test and residual test and the best final model obtained. Practical implications: The conclusion is that the weight and the order of the containers are the factors that most take influence the productivity of both the CY (Container Yard) and the ship. The value of the influence of the significance of determination is 957 or equal to 95.7%, so that means that one independent variable has a significant influence of 19% on the existing dependent variable. Paper type: Research paper.